(untitled) (International Journal of Biomedical and Advance Research, 2015)
This study has been undertaken to find association between socioeconomic status and diabetes mellitus in perimenopausal women in an urban slum of Mumbai. The cross-sectional community-based descriptive epidemiological study was conducted in slum area during the period of January 2012 to June 2013. Out of 61 diabetic patients, 14.8% were in class I, 18% were in class II, 16.4% were in class III and remaining 41% were in class IV and 9.8% were in class V. Out of 389 nondiabetic subjects, 5.1% were in class I, 6.7% were in class II, 20.6% were in class III, 46.3% were in class IV and 21.3% were in class V. There was significant statistical association between socioeconomic status and diabetes mellitus among perimenopausal women in an urban slum.